2003
DOI: 10.1091/mbc.e02-10-0633
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Biogenesis Occurs in an Unsynchronized Manner in Close Association with the Endoplasmic Reticulum in Temperature-sensitiveYarrowia lipolyticaPex3p Mutants

Abstract: Pex3p is a peroxisomal integral membrane protein required early in peroxisome biogenesis, and Pex3p-deficient cells lack identifiable peroxisomes. Two temperature-sensitive pex3 mutant strains of the yeast Yarrowia lipolytica were made to investigate the role of Pex3p in the early stages of peroxisome biogenesis. In glucose medium at 16°C, these mutants underwent de novo peroxisome biogenesis and exhibited early matrix protein sequestration into peroxisome-like structures found at the endoplasmic reticulum-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 46 publications
3
26
0
1
Order By: Relevance
“…N.S., not significant; **P,0.01. pex3D cells of Y. lipolytica failed to assemble functional peroxisomes and showed a general mislocalization of peroxisomal matrix proteins to the cytosol (Bascom et al, 2003). We speculate that the elongated fluorescent structures observed in pex11D and pex3D cells expressing genomically integrated POT1-GFP are an artifact of oligomerization of Pot1p-GFP that is mislocalized to the cytosol.…”
Section: Y Lipolytica Pex11 Protein Family Members Are Peroxisomal Imentioning
confidence: 86%
See 1 more Smart Citation
“…N.S., not significant; **P,0.01. pex3D cells of Y. lipolytica failed to assemble functional peroxisomes and showed a general mislocalization of peroxisomal matrix proteins to the cytosol (Bascom et al, 2003). We speculate that the elongated fluorescent structures observed in pex11D and pex3D cells expressing genomically integrated POT1-GFP are an artifact of oligomerization of Pot1p-GFP that is mislocalized to the cytosol.…”
Section: Y Lipolytica Pex11 Protein Family Members Are Peroxisomal Imentioning
confidence: 86%
“…The functions of the peroxins Pex3p and Pex19p in these processes are well documented in different eukaryotes (Smith and Aitchison, 2013;Tabak et al, 2013). In Y. lipolytica, pex3D cells lack any peroxisomal structures (Bascom et al, 2003) and pex19D cells, although they do contain morphologically identifiable peroxisomes, mislocalize peroxisomal matrix proteins to the cytosol (Lambkin and Rachubinski, 2001). We assessed the localization of Pex11p-mC, Pex11Cp-mC and Pex11/25p-mC in pex3D and pex19D cells by confocal microscopy.…”
Section: Y Lipolytica Pex11 Protein Family Members Are Peroxisomal Imentioning
confidence: 99%
“…There is certainly increasing data to suggest that there are subdomains of the ER such as specific regions that are continuous with a peroxisomal reticulum from which a major source of peroxisomes can originate (Bascom et al, 2003;Hoepfner et al, 2005), as well as ER subdomains that give rise to lipid droplets (Ozeki et al, 2005;Robenek et al, 2004). In addition there is now increasing evidence to suggest that there are regions of the ER that are in direct contact with the plasma membrane as well as in intimate association with mitochondria (Levine and Rabouille, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast Yarrowia lipolytica, the peroxisomal membrane proteins Pex2p and Pex16p were shown to traffic through the ER and to acquire core N-linked glycosylation (7). Findings supporting de novo peroxisome biogenesis in close association with the ER were obtained in cells of Y. lipolytica temperature-sensitive for Pex3p function (8), and studies in the plant Arabidopsis showed that peroxisomal ascorbate peroxidase localized to a subdomain of rough ER that could serve as a compartment for posttranslational sorting to peroxisomes (9). In mouse dendritic cells, the peroxisomal membrane proteins Pex13p and PMP70 were found in subdomains of the ER that extended to a peroxisomal reticulum from which mature peroxisome arose (10).…”
mentioning
confidence: 95%